Lingkungan Kerja dan Pengalaman Kerja Terhadap Motivasi Kerja Pengawai: Peran Mediasi Kecerdasan Emosional - Mauludyah, Afiatul; Sari, Niki Puspita; Muhammad, Helmi (DIALEKTIKA: Jurnal Ekonomi dan Ilmu Sosial, 2025)
This study aims to determine and analyze the influence of the work environment and work experience on emotional intelligence and work motivation of employees of the Indonesian Agro Niaga Cooperative (KANINDO) Syariah East Java. This study uses a quantitative approach by distributing questionnaires to the entire population. Data analysis uses Partial Least Square (PLS) through the SmartPLS application. The results of the study indicate that the work environment has a significant effect on emotional intelligence, work experience has a significant effect on emotional intelligence, the work environment has a significant effect on employee work motivation, work experience has a significant effect on employee work motivation, emotional intelligence has a significant effect on employee work motivation, emotional intelligence cannot mediate the influence of the work environment on employee work motivation, and emotional intelligence can mediate the influence of work experience on employee work motivation at KANINDO Syariah East Java.